"Metal-free'' synthesis of 1,2,3-triazoles via tandem azidation, intramolecular [3+2]-cycloaddition and aromatization of ethyl acrylate derivatives - Kumar, B. Senthil; Gadakh, Sunita; Sudalai, Arumugam (Tetrahedron Letters, 2018)
An efficient ``one-pot'' method for the synthesis of substituted 1,2,3-triazole derivatives in excellent yields as single regioisomer is reported. The key transformation involves an atom-efficient tandem azidation, intramolecular [3+2]-cycloaddition and aromatization of acrylate derivatives on treatment with NaN3 in DMF under mild conditions. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Intramolecular cycloaddition; Regioselective; Tandem azidation; triazoles

Concise formal synthesis of (-)-(6R,11R,14R)-colletallol via D-proline catalysed alpha-aminooxylation-Wittig olefination strategy - Dey, Soumen; Gadakh, Sunita; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2019)
An efficient enantioselective formal synthesis of marine macrolide (-)-(6R,11R,14R)-colletallol has been achieved starting from commercially available raw materials. The key reactions include the D-proline catalyzed a-aminooxylation of aldehyde followed by Horner-Wardsworth-Emmons olefination in a sequential fashion to give the macrolide key intermediate 5 in high enantiomeric purity (97% ee) and high overall yield (32%).
Keywords: alpha-aminoxylation; Asymmetric synthesis; Enantioselectivity; Natural products; organocatalysis

Proline catalyzed sequential alpha-amination/ Prins/ Ritter amidation of aldehydes: new method of construction of tetrahydropyran units - Ahuja, Brijbhushan; Gadakh, Sunita; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2019)
An efficient ``one-pot'' synthetic method toward highly substituted tetrahydrofuran (THP) units is reported. The key transformation involves an atom-efficient sequential proline catalyzed alpha-amination of aldehydes to give alpha-aminated aldehydes in situ and the subsequent cyclomerization with homoallylic alcohols under Prins/Ritter conditions. Notably, this method provides access to enantiopure 1,2-syn and 1,4-anti diamino alcohols via reductive ring opening of THP units.
Keywords: alpha-aminoxylation; organocatalysis; Proline catalyzed; sequential; tetrahydropyran unit